Effect of oxygen flow rate on physical properties of Al-doped ZnO transparent conducting films prepared by reactive dc magnetron sputtering using metallic Zn:Al target - T Gaewdang; Ng Wongchaoen (My University, 2020)
Abstract In this work, Al-doped ZnO transparent conducting thin films were prepared by a reactive dc magnetron sputtering method on slide glass substrate using single metallic Zn:Al (2 wt.% Al) target with the oxygen flow rate 1, 3, 5, 7 and 9 sccm, respectively. From XRD patterns, the films prepared at R(O 2 ) of 1 sccm showed amorphous characteristics. In contrast, the films prepared at R(O 2 ) of 3, 5, 7 and 9 sccm showed the preferred orientation (002) plane of hexagonal structure. Surface morphology and diameter of nanocolumns of the films were observed by AFM and FESEM. From transmittance spectra, energy gap value was found to vary between 3.24 and 3.32 eV. Electrical resistivity and Hall effect measurements were performed on the films with van der Pauw configuration. The temperature-dependent conductivity was performed in the range 20-300 K. Three types of conduction mechanisms were expected. Thermally activated band conduction at the high temperature range (250-300 K), Mott variable-range hopping (Mott-VRH) at the low temperature range (100-210 K) and Efros-Shklovskii variable-range hopping (ES-VRH) at the very low temperature range (<100 K) can be found in the films prepared with different oxygen flow rate conditions. Except for the oxygen flow rate at 5 sccm, the behavior of weakly localized electrons was observed. Then, the sets of parameters explaining the properties of localized electrons in each conduction regime were determined. The results indicated that the reactive dc magnetron sputtering using a single metallic Zn:Al (2 wt.% Al) target is suitable for TCO films since it can be easily obtained at low temperatures with good physical properties.
Keywords: Variable-range hopping; Atmospheric temperature range; Cavity magnetron; ZnO doping and properties